HUBUNGAN KADAR LOWDENSITY LIPOPROTEIN CHOLESTEROL DENGAN KEJADIAN DAN KEPARAHAN STROKE AKUT - Azwita Effrina Hasibuan*, Aida Fitri*, Khairul Putra Surbakti*, Aldy Safruddin Rambe* (NEURONA, 2015)
INTRODUCTION THE ROLE OF SERUM CHOLESTEROL IN STROKE ETIOLOGY IS STILL UNCERTAIN STUDIES FOCUSING ON ASSOCIATION BETWEEN LOWDENSITY LIPOPROTEIN LDL CHOLESTEROL AND ACUTE STROKE ARE STILL RARE AND INCONSISTENT